Design and Fabrication of Parallel Curved Spring for Nonlinear Energy Harvester. (2015) - Yamamoto, Koki; Fujita, Takayuki; Badel, Adrien; Kanda, Kensuke; Maenaka, Kazusuke
Abstract: In this paper, a design improvement of combination spring that consists of linear resonator and curved beam for nonlinear vibration energy harvesting is described. The intrinsic curved beam for snap-through buckling acts as mechanical frequency converter (MFC) that applies high frequency acceleration to the linear resonator. We newly designed the parallel curved beams to reduce the force required for snap-through and maximum stress during snap-through behavior. From FEM analyses, the force and the stress are reduced from 35.4 mN to 10 mN and from 350 MPa to 200 MPa, respectively.